Willingness to pay for a telepharmacy-based patient medication counseling service and its determinants in a tertiary hospital in Manila, Philippines - Cai, Natasha Ysabel Y.; Robles, Yolanda R. (Manila College of Pharmacy, University of the Philippines Manila, 2025)
Patient medication counseling (PMC) is a service offered by pharmacists that aims to optimize treatment outcomes and help the patient make the best use of his or her medications. However, in the Philippines, there is still no remuneration assigned for PMC leading to negative consequences such as the lack of practice of the service. This study aims to gather the willingness to pay (WTP) of patients for PMC and to determine the factors that can influence the WTP. The study aims to gather the WTP through the double- bounded dichotomous choice approach under the contingent valuation method. Patients were asked if they were willing to pay P25, P50, and P100 and were made to answer a survey questionnaire asking for the patient’s sociodemographic characteristics, satisfaction with the service, perceived importance of the information attained from PMC, and the attitude towards the activities included in PMC. Multiple regression was done to determine the correlation between the factors and WTP. A total of 40 (33.33%) out of 120 patients responded, with the significant variables for WTP P50 being receiving information on how to avoid side effects and the significant variables for WTP P100 being biological sex, the desire to have the PMC service available in the locality or area, and how to avoid side effects. The desire to have the PMC service available in the patient’s locality or area may have been a determinant due to the reason that most patients from the Philippine General Hospital come from remote areas where sources of medicine information may be lacking. The convenience of using telepharmacy and specifically, telecounseling may allay the fear of side or adverse effects among patients since they will know how to avoid side effects. It is recommended that future researchers wanting to conduct a similar study will use a larger sample size for generalizability and have pay patients as the population of interest. Further, it is recommended that pharmacy owners, pharmacists, and policy makers consider having the service offered all over the country to encourage the pharmacists to provide telecounseling and make patients more willing to pay for this service. Professional organizations should provide training through continuing professional education to enhance the counseling competency of pharmacists so that they could contribute to positive health outcomes.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2025
Keywords: Telepharmacy -- Patient counseling -- Willingness to pay -- Philippines; Pharmaceutical services -- Economic evaluation -- Hospitals, Tertiary -- Philippines; Pharmacist and patient -- Telepharmacy -- Counseling services; Patient medication counseling; telepharmacy-based patient medication counseling; willingness to pay; determinants